PENINGKATAN KETERAMPILAN MENULIS CERPEN MELALUI PENERAPAN METODE PETA KONSEP SISWA KELAS X SMA NEGER 3 POLEWALI MANDAR - GISMAN GISMAN (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2012)
This research aimed to kuwing the skill level of SMA Negeri 3 Polewali students when they are writing short story by applying draft Maping Method where in this research will discribe and explain the mastery of writing skill short story, a bout pre writing step, writing short story step, revision of writing step and the mastery writing short story skill using aplication draf Maping Method. Kinds of research is class action research using subjek research are 32 students. Data are needed is first siclus action and secoud siclus action, observation interviwier, reseorching instrument and documentation by descriptive statistic and quality approach. Research result shoving that skill level writing short story at X class of SMA Negeri 3 Polewali Mandar by applying Maping consept are; (1) in first all aspect are payed attention every student is active it’s the same at the second siclus, but in the second siclus thera are some revision it’s not there in first siclus (cycle), (2) in the evaluation step of student skill in writing short story are increasing very significancy where in the first siclus only 20 student or 62, 5% ore passed (completenness) an 12 aren’t passed or 37,5% and text evaluation by teacher there are 22 student in good answered or 68,75% and 10 students aren’t passed or 31,25, and the end of second siclusthere are some increasing or 87,5% and 4 students aren’t in creasing or 12%. For all student evaluation achieve 100% student’s are passed. Find out resume of both siclus one and two is consep Maping Method are suitable using in increasing writing skill student.